Multimodal Analysis of the Tissue Response to a Bone-Anchored Hearing Implant: Presentation of a Two-Year Case Report of a Patient With Recurrent Pain, Inflammation, and Infection, Including a Systematic Literature Review - Johansson, Martin L.; Calon, Tim G.A.; Omar, Omar; Shah, Furqan A.; Trobos, Margarita; Thomsen, Peter; Stokroos, Robert J.; Palmquist, Anders (Frontiers in Cellular and Infection Microbiology, 2021)
Osseointegration is a well-established concept used in applications including the percutaneous Bone-Anchored Hearing System (BAHS) for auricular rehabilitation. To date, few retrieved implants have been described. A systematic review including cases where percutaneous bone-anchored implants inserted in the temporal bone were retrieved and analyzed was performed. We also present the case of a patient who received a BAHS for mixed hearing loss. After the initial surgery, several episodes of soft tissue inflammation accompanied by pain were observed, leading to elective abutment removal 14 months post-surgery. Two years post-implantation, the implant was removed due to pain and subjected to a multiscale and multimodal analysis: microbial DNA using molecular fingerprinting, gene expression using quantitative real-time polymerase chain reaction (qPCR), X-ray microcomputed tomography (micro-CT), histology, histomorphometry, backscattered scanning electron microscopy (BSE-SEM), Raman spectroscopy, and fluorescence in situ hybridization (FISH). Evidence of osseointegration was provided via micro-CT, histology, BSE-SEM, and Raman spectroscopy. Polymicrobial colonization in the periabutment area and on the implant, including that with Staphylococcus aureus and Staphylococcus epidermidis, was determined using a molecular analysis via a 16S-23S rDNA interspace [IS]-region-based profiling method (IS-Pro). The histology suggested bacterial colonization in the skin and in the peri-implant bone. FISH confirmed the localization of S. aureus and coagulase-negative staphylococci in the skin. Ten articles (54 implants, 47 patients) met the inclusion criteria for the literature search. The analyzed samples were either BAHS (35 implants) or bone-anchored aural epitheses (19 implants) in situ between 2 weeks and 8 years. The main reasons for elective removal were nonuse/changes in treatment, pain, or skin reactions. Most samples were evaluated using histology, demonstrating osseointegration, but with the absence of bone under the implants’ proximal flange. Taken together, the literature and this case report show clear evidence of osseointegration, despite prominent complications. Nevertheless, despite implant osseointegration, chronic pain related to the BAHS may be associated with a chronic bacterial infection and raised inflammatory response in the absence of macroscopic signs of infection. It is suggested that a multimodal analysis of peri-implant health provides possibilities for device improvements and to guide diagnostic and therapeutic strategies to alleviate the impact of complications.